MICROGLIAL ACTIVATION AS A CENTRAL MECHANISM IN NEURODEGENERATION AND PSYCHIATRIC DISORDERS: FROM MOLECULAR SIGNALING PATHWAYS TO TRANSLATIONAL THERAPEUTIC TARGETS (Global Conference on Medical and Health Sciences, 2026)
Microglial activation has emerged as a pivotal process in the pathophysiology of both neurodegenerative and psychiatric disorders, reflecting the growing recognition of immune mechanisms in brain function and dysfunction. Microglia, as the primary immune cells of the central nervous system, play a dual role in maintaining neural homeostasis and mediating inflammatory responses. While acute activation is essential for neuroprotection and tissue repair, chronic or dysregulated microglial activity has been increasingly implicated in neuronal damage, synaptic dysfunction, and disease progression.